Molecular regulation after mucosal injury and regeneration in ulcerative colitis - Zheng, Lie; Duan, Sheng-Lei; Wen, Xin-Li; Dai, Yan-Cheng (Frontiers in Molecular Biosciences, 2022)
Ulcerative colitis is a chronic nonspecific inflammatory disease with a complex etiology. Intestinal mucosal injury is an important pathological change in UC. Lgr5+ Intestinal stem cells (ISCs) exhibit self-renewal and high differentiation potential and play important roles in the repair of intestinal mucosal injury. Moreover, LGR5+ ISCs are intricately regulated by both the Wnt/β-catenin and Notch signaling pathways, which jointly maintain the function of LGR5+ ISCs. Combination therapy targeting multiple signaling pathways and transplantation of LGR5+ ISCs may lead to new clinical therapies for UC.